Percepción de la calidad del cuidado de enfermería en un contexto hospitalario durante la pandemia COVID-19 - Canaza, Allison (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The perception of the quality of nursing care in hospitalized people has been unknown over time in different parts of the world, but the appearance of this novel disease of COVID-19 caused the health system to be severely affected and criticized is For this reason, the study was carried out with the objective of determining the perception of the quality of nursing care in people hospitalized in the COVID-19 area of ​​the III Yanahuara hospital, Arequipa 2021. The research was quantitative and descriptive with a non-experimental cross-sectional design. ; the population consisted of 84 hospitalized people with a sample of 74; the type of sampling was non-probabilistic for convenience according to inclusion and exclusion criteria; the technique used was the survey and the Caring Assessment Instrument (Care-Q) questionnaire as an instrument, which has validity and reliability. For data processing, the statistical software program SPSS version 24 was used. The most important results on the perception of nursing quality reveal that 51.4% consider the quality of care to be good. Regarding the dimensions: "It is accessible", "It explains and facilitates" and "It monitors and follows up", 47.3%, 58.1% and 40.5% respectively, perceive it as good quality; on the contrary, in the dimensions "Comforts", "Anticipates" and "Maintains relationship of trust" 70.3%, 55.4% and 54.1% respectively indicate poor quality. It is concluded that the majority of hospitalized people perceive nursing care as good quality.